Information of the Financial Statements Disclosures - Case of Albania - MITI, Mirela UJKANI; Çika, Nertila; Dhamo, Sotiraq (European Journal of Economics and Business Studies, 2018)
Since 2008 in Albania, financial reporting is carried out based on international standards and national accounting standards, which are in compliance with International financial reporting standards. In our paper, we want to focus on the "Financial Statements Disclosures" as one of the components of the full package of financial statements. Often there is an erroneous view or attitude that compiles disclosures is something simple and easy. But even for their preparation, the accounting principles and rules should be strictly followed. Through the literature review we will highlight the role and importance of preparing of the financial statements disclosures on financial reporting, the care that should be shown in their preparation and the importance they have for users of financial statements. This also for the fact that, as simple as it may seem in its preparation, this statement has a high level of significance, and may even serve as an "indicator" for detecting fraud, assisting decision-making processes, and so on. The objectives of our paper will be realized through comparative, descriptive and statistical analyzes, using primary and secondary data. Primary data will be provided by the questionnaire addressed to target groups: accountants-because they prepare disclosures; auditors and tax inspectors-because they are the users of financial statements disclosures as they use these notes to understand the truth and credibility but also to discover frauds and mistakes. Secondary data will be gained from the literature review and the national accounting standards study of our country. The primary data analysis will serve first to understand the level of preparation of the financial statements disclosures and then to understand the role and importance of their information in the preparation of the full set of financial statements, with the purpose of giving the true and fair view of the activity of the entity, thus contributing to the increase of transparency. Secondary data analysis will serve to understand better the theoretical framework for the disclosures and the information that they carry. In the end, we will provide necessary recommendations regarding the disclosures and information they need to carry to ensure a higher quality of financial reporting.
Keywords: financial reporting, disclosures, accounting, users of accounting information.